2021
DOI: 10.1155/2021/9931885
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Aspirin on Myocardial Ischemia-Reperfusion Injury in Rats through STAT3 Signaling Pathway

Abstract: Objective. To investigate the role and mechanism of aspirin in myocardial injury induced by myocardial ischemia-reperfusion in rats through STAT3 signaling pathway. Methods. Sixty rats were randomly divided into three groups: the sham operation group, MI/R group, and MI/R+aspirin group (aspirin group). The rats in the sham operation group did not ligate the LAD coronary artery, while the aspirin group ligated the LAD coronary artery, which caused the suture to be loosened after 30 minutes ischemia, and 60 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Although long term use of aspirin causes significant gastric mucosal injury, it is still the preferred drug for treating CHD because it is highly effective in suppressing thrombosis through suppression of COX-1 and TXA2 ( Basili et al, 2014 ). A recent randomized controlled trial demonstrated that aspirin protected the myocardium from I/R injury by inhibiting cardiomyocytes apoptosis ( Wu et al, 2021 ). This suggested that aspirin protects against myocardial dysfunction through multiple mechanisms, such as suppression of thrombosis and cardiomyocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although long term use of aspirin causes significant gastric mucosal injury, it is still the preferred drug for treating CHD because it is highly effective in suppressing thrombosis through suppression of COX-1 and TXA2 ( Basili et al, 2014 ). A recent randomized controlled trial demonstrated that aspirin protected the myocardium from I/R injury by inhibiting cardiomyocytes apoptosis ( Wu et al, 2021 ). This suggested that aspirin protects against myocardial dysfunction through multiple mechanisms, such as suppression of thrombosis and cardiomyocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Furthermore, a recent study on rats showed that in the setting of transient ligation of the left anterior descending coronary artery (LAD), aspirin treatment 10 minutes before reperfusion results in cardioprotection (i.e., less apoptosis, improved function, and decreased infarct size) through activation of JAK2/STAT3 signaling in myocardial tissue. 40 …”
Section: Introductionmentioning
confidence: 99%
“…All of these cardiovascular dysfunctions can provoke cell death and tissue damage which in turn further increase infarct size. To date, MIRI currently has been considered a major biological event depressing the effect of clinical treatment of cardiovascular diseases [ 10 ]. Although strenuous efforts had been made to develop treatment strategies for MIRI, exploring a promising drug and clarifying the therapeutic mechanisms of MIRI are urgently needed.…”
Section: Introductionmentioning
confidence: 99%